Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Publisher: Recherches amérindiennes au Québec
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)